Sie sind auf Seite 1von 11

M. M. ALI Page No.:1/11

TIME VARYING FIELDS

Introduction

In this chapter we will find that a time varying electric field can be produced by a time varying magnetic field and vice versa. In fact, if there exists a time varying electric (magnetic) field in a region, there also exists a time varying magnetic (electric) field in that region. We will refer to an electric field due to time varying magnetic field as an induced electric field. The line integral of such an induced electric field is called the induced emf.

3.1 Motional electromotive force

Let us consider a conductor moving with a uniform velocity u in the magnetic field B as shown in the adjacent figure. The magnetic force acting on each of the free electrons in

the conductor is

charge of an electron. Under the influence of this force the electrons within the conductor will move from right to left. Such a migration of electrons will result in a net negative charge at the left end of the conductor and a net positive charge at the right end.

F = −eu × B = −euBa , where –e is the

y The workdone by an external source to move the electron a distance dl is dW m = -F•dl= e(u×B)•dl =eE•dl (The electric field is defined as the force on a positive unit charge and hence E=u×B). Therefore the voltage difference between two ends of the conducting bar, named as induced voltage, is given by

e

m

= dW
m
=
E • dl =
e

(u × B) dl

.

(61a)

As this induced voltage e m is due to the motion of conducting bar in the magnetic field, it

is called the motional electromotive force. Let us now consider the case where a conductor is sliding freely over a pair of stationary conductors as shown below. The electric circuit is closed by connecting a resistance between the far ends of the two stationary conductors. For the considered problem

e

m

=

(u

×

B)

dl

=

a

b

uBdy

=

uB(a

b)

=− uBL

(61b)

which indicates that the terminal b is at higher potential than a. As in calculating voltage we have to move a unit positive charge against E, the integration is carried out from b to

a.

M. M. ALI Page No.:2/11

The voltage e m induced in the bar results in a current I in the circuit which is known as induced current. This current produces a magnetic flux that will oppose the original magnetic flux B and satisfies Len’s law.

3.2 Maxwell’s equation from Faraday’s law of electromagnetic induction

As the sliding conductor in the above figure moves a distance dx in the x-direction in time dt, the increase in cross-sectional area made by the circuit is given by ds=Ldx. Now

the change in magnetic flux passing through the plane

ds = −Ldxa

z

is

φ

d

=

B

ds

= BLdx

d

φ

dx

= BL

dt

dt

= BLu

Therefore from (61b) we obtain equation of the induced voltage as

e

i

=−

d φ

dt

.

(62)

electromagnetic

induction. It states that the induced emf around a closed path is equal to the negative rate of change of the magnetic flux with respect to time passing through the area enclosed by the path.

Equation (62) is a mathematical definition of Faraday’s Law of In (62) e i = ∫ E • dl and φ
d
B
E
• dl =−
d
S
dt
S

=

S

B

dS

(63a)

Using Stokes’s theorem the above equation can be written as

∇ × E = −

dB

dt

(63b)

It becomes ∇×E=0 for time invariant or dc field. We identify eqs. (63a) and (63b) as Maxwell’s equations in integral and differential or point forms, respectively. The induced emf in a stationary circuit caused by a time-varying magnetic field can also be calculated from (62) as

e

i

φ

d

d

= e =− =−

t

dt

dt

s

B

ds

(64)

where e t is termed as transformer emf. In case of moving circuit in a time varying magnetic field, the induced emf is therefore given by d
e i =−
B
d
s
+
(
v
×
B
)
dt
s
L
d
E
• =−
dl
B
d
s
+
dt
s
L

dl

(

u

×

.

B

)

dl

Now the application of Stoke’s theorem yields

s

(

)

∇× • =−

E

ds

d

dt

s

B

d

∴∇× =−

E

d

dt

B

(

+∇× ×

u

s

[

+ ∇×

s

B

)

(

u

×

B

)

]

ds

(65)

M. M. ALI Page No.:3/11

This equation is the most general form of Maxwell’s equation (Faraday’s law) in the point form.

3.3 Displacement current and Maxwell’s equation from Ampere’s Circuital law

The ampere's circuital law for static field is no longer useful in time varying fields as is shown below:

Taking the divergence of the ampere's circuital law give by eq (49) and using the continuity equation (32) we have

∇• (∇× ) =∇• =−

H

J

d ρ

v

d ρ

v

dt

dt

= 0

That is, equation (49) leads to steady state conditions in which charge density is not time varying function. Therefore, for time dependent fields eq (49) needs some modifications. Maxwell suggested that the definition of total current density of ampere's circuital law is incomplete and advised to add something to J. If it is assumed to be J , eq (49) becomes

∇× H = J + J

d

ρ

v

⇒ ∇ • ∇ × = ∇ •

H

(

J

)

⇒ ∇ • ′ = −∇ • =

J

J

d (

∇• D

)

+

J ′=

d D

+

dt

)

(

J

0

= ∇ •

(

J

J

)

⇒∇• J ′=

dt

dt

Since J ' arises due to the variation of electric displacement (electric flux density) D with time, it is termed as displacement current density. It is as effective as J. The modified Ampere's circuital law (Maxwell’s equation), therefore, for time varying field takes the following form

∇× H = J +

dD

dt

(66a)

Applying Stoke’s (66a) can be given in integral form as d
D
d
D
H
dl
=
(
J
+
)
ds
= +
I
dt
dt
L
s
s

ds

(66b)

The important conclusion that can be drawn from eq (65) is that, since displacement current is related to the electric field, it is not possible in case of time varying fields to deal separately with electric and magnetic fields but, instead, the two fields are interlinked giving rise to electromagnetic fields. It is to be noted that, in a good conductor J ' is negligible compared to J at frequency lower than light frequencies (10 15 Hz).

Example 3.1 A copper strip of length L pivoted at one end is rotating freely with an angular velocity ω in a uniform magnetic field, as shown in the following figure. What is the induced emf between the two ends of the strip? Solution : The velocity at any radius ρ is u=ρω a φ .
Therefore, the induced electric field E=u×B= ρωB a ρ.
Using (65) we obtain
0
d
B
d
s
+
(
u
×
B
)
• = ρω
d l
B
a
• ρ
d
a
e iab = −
ρ
ρ
dt
s
L
L
1
2
=− ω BL
2

M. M. ALI Page No.:4/11

The result shows that the b end is at higher potential than the pivoted end. Example 3.2 A copper strip of length 2L pivoted at the midpoint is rotating with an angular velocity ω in a uniform magnetic field as shown in the following figure. Determine the induced emf between the two ends. Solution: The problem is similar to that in the previous example
except that we have to consider two arms of equal
length L pivoted at the centre. Therefore two tips are
2
at equal voltage of
1 ωBL volts with respect to the
2
midpoint. Therefore the potential difference i.e., the
induced emf between the ends is zero.

Example 3.3 A copper conductor is placed in such a way that the magnetic field is perpendicularly outward to the surface contains the conductor as shown in the following figure. Determine induced emf e 12 . Solution:

B= B 0 sin ωt a z 1
B
b
2

z

sinω

t

a

z y

x

dxdy

a

z

ω

=−

0

e 12 a
Using (65) we obtain
a
b
d
d
=−
B
d
s
+
(
u
×
B
)
• =−
d
l
∫∫
B 0
e 12
dt
dt
s
L
0
0

B ab

t

cosω

The polarity of the terminals will be such that, the current due to this voltage will set up a magnetic field which will oppose the original field. Example 3.4 A circular conducting loop of radius 40 cm lies in the x-y plane and has a resistance of 20 . If the magnetic flux density in the region is given as B=0.2 cos 500t a x +0.75 sin 400t a y +1.2 cos 314t a z Tesla. Determine the effective value of the induced current in the loop. Solution: The differential surface area of the loop is ds=ρdρdφ a z . Therefore from (65) d
d
e
=−
B
ds
+
(u
×
B)
• =−
d
l
B
ds
i
dt
dt
s
L
s d
Now
B
=−
100sin 500
t
a
+
x
dt
0.4 2
π
d
∴ e
=−
B
d s
=
376.8
∫∫
i
dt
s 0
0
and i
= 9.47 sin 314 t
 300 cos 400 t a y − 376.8sin 314 t a z sin 314 ρρφ t d d = 189.4sin 314 t

Therefore the required result is 6.7 Amps.

Example 3.5 The magnetic field in free space is given by H=H 0 sinθ a y A/m, where θ= ωt-βz, and β is a constant. Determine the displacement current and E.

M. M. ALI Page No.:5/11

Solution: As the conduction current J in free space is zero, we obtain from Maxwell’s equation that a
a
a
x
y
z
d
D
d
D
d
d
d
d
d
∇× =
H
=
=−
H
sin
θ
a
+
0
x
dt
dt
dx
dy
dz
dz
dx
0
H
sin
θ
0
0
2
=
β
H
cos
θ
a
A/m
0
x
1
D
1
Again
D
=
β
H
cos
θ
dt
a
=
β
H
sin
θ
a
⇒ =
E
=
β
H
0
x
0
x
ω
ε ωε
0
0

H

0

sin

0

sin

θ

a

θ

a

z

x

V/m

3.4 Maxwell’s equations in time domain

By studying the physical properties of electric (E-field) and magnetic (B-field) fields we have been able to describe these properties by four, relatively simple, equations known as Maxwell’s equations. These four fundamental equations of electromagnetism can be expressed in both an integral and differential form as tabulated below:

 Sl No. Point/Differential form Integral form Equation No. 1) ∇•D=ρ v ∫ D ∫ • ρ = v ds dv (67) s v 2) ∇•B=0 ∫ B • ds = 0 (68) s 3) ∇× E =− dB dt ∫ L ∫ s d B E • dl =− dt • d s (69) 4) ∇× H = J + dD d D ∫ H • l = (J + d ∫ dt L s ) • d s (70) dt

Equation (67) results from Coulomb’s and Gauss’s laws and states that free charges act as sources or sinks of D. It suggests that the total electric flux density or total electric displacement through the surface enclosing a volume v is equal to the total charge within the volume. Equation (68) arises from the application of Gauss’s law to magnetic fields and the non- existence of magnetic monopoles. There are no sources or sinks of B. This equation suggests that the net magnetic flux emerging through any closed surface is zero. Equation (69) describes Faraday’s law of electromagnetic induction and states that an electromotance is produced in a circuit when the magnetic flux through the circuit changes. It suggests that the electromagnetic force around a closed path is equal to the time derivative of the magnetic flux density through any surface bounded by the path. Equation (70) describes Ampere’s circuital law (which is derived from the Biot-Savart law) and states that the magnetomotive force around a closed path is equal to the conduction current J=σE plus the time derivative of the electric flux density through any surface bounded by the path. In vacuum/free space ρ v =0, J=0, ε=ε 0 and µ=µ 0 . Therefore, in vacuum the Maxwell's equations take the following forms:

M. M. ALI Page No.:6/11

 Sl No. Point/Differential form Integral form Equation No. 1) ∇•D=0 ∫ D • d s = 0 s 2) ∇•B=0 ∫ B • ds = 0 s 3) E ∇× =− dB d H ∫ L ∫ s d H E • dl =− µ 0 dt • d dt =−µ 0 dt s 4) ∇× = H dD dt =ε 0 d E dt ∫ L d E H • d = l ε 0 dt ∫ s • d s

3.5 Maxwell’s equations in frequency domain

Assuming the fields are varying harmonically with time as e jωt , the maxwell’s equations are given by

 Sl No. Point/Differential form Integral form Equation No. 1) ∇•D=ρ v ∫ D ∫ • ρ = v ds dv (71) s v 2) ∇•B=0 ∫ B • ds = 0 (72) s 3) ∇× E =− jωB ∫ L E dl • =− ∫ jω B s • ds (73) 4) ∇ × H = (σ + jωε )E ∫ L H • l = ( + d σ jωε ) ∫ s E • ds (74)

3.6 Maxwell’s equations in phasor forms

In case the field quantities are sinusoidally time varying, the electric field E can be expressed as E(x, y, z, t)=E x (x, y, z, t) a x + E y (x, y, z, t) a y + E z (x, y, z, t) a z

where E x =E xm cos(ωt+θ x ), E y =E ym cos(ωt+θ y ), E z =E zm cos(ωt+θ z ). Here the magnitudes E xm , E ym , E zm and the phase angles θ x , θ y , θ z are independent of time but may depend on spatial coordinates, e.g., E xm (x, y, z), θ x (x, y, z). Now E x can be expressed as E x = E xm cos(ωt+θ x )=Re[E xm e j(ωt+θx) ]= Re[E xm e jωt e jθx ] and similarly E y and E z . Therefore E x , E y and E z can be expressed in phasor form as follows: Ê x = E xm e jθx = E xm ∠θx, Ê y = E ym e jθy = E ym ∠θy, Ê z = E zm e jθz = E zm ∠θz. Therefore E(x, y, z, t)= E xm cos(ωt+θ x ) a x + E ym cos(ωt+θ y ) a y + E zm cos(ωt+θ z ) a z

= Re[E xm e j(ωt+θx) ] a x + Re[E ym e j(ωt+θy) ] a y + Re[E zm e j(ωt+θz) ] a z

= Re[Ê x e jωt ] a x + Re[Ê y e jωt ] a y + Re[Ê z e jωt ] a z

= Re[(Ê x a x + Ê y a y + Ê z a z ) e jωt ]= Re[Ê e jωt ]

If we remember that the fields are real part of their exponential form, we may consider

the fields as follows:

E(x, y, z, t)= Ê(x, y, z) e jωt Likewise

M. M. ALI Page No.:7/11

H(x, y, z, t)= Ĥ(x, y, z) e jωt

D

B

(x, y, z, t)

(x, y, z, t)

=

=

ˆ

D (x, y, z)e

j

t

ω

ˆ

B (x, y, z)e

j

t

ω

d

dt

In this cases,

varying field is jω times the field. Therefore, the Maxwell's equations in phasor form can be expressed as:

that is, the first derivative of a sinusoidal

ˆ

B

(x, y, z)e

j

t

ω

ˆ

jωB (x, y, z)e

j

t

ω

=

 Sl No. Point/Differential form Integral form Equation No. 1) ∫ ˆ ∫ (75) ˆ ∇• D = ρˆ D ˆ ρ v dv v • d s = s v 2) ˆ ∫ s ˆ (76) ∇• B = 0 B • d s = 0 3) ˆ B ˆ ∫ L ˆ j ω ∫ s ˆ (77) ∇× =− jω E E • dl =− B • ds 4) ˆ ˆ ∫ L ˆ ∫ s ˆ (78) ( ∇ × = σ + jωε H ) E H • ( d σ jωε l = + ) E • ds

3.7 Boundary condition for electromagnetic field

For the time varying tangential component of E-field let us apply the Faraday’s law (61) along the rectangular path as the closed loop in figure (a). If its height h is made infinitesimally small then the only contribution to the line integral of the left side of (61) is along the top and bottom edges of length dL and the right hand side becomes zero as the area dLxh is vanishingly small.

L

E

dl

E 1t =E 2t

=

E

1

•−

(

dL

)

+

E

2

(

dL

)

D 1t /ε 1 =D 2t /ε 2

=−

E

1t

dL

+

E

2t

dL

=

0

(79)

where E t is the tangential component of E. Hence E 1t =E 2t ; the tangential component of E is continuous across any interface. For the time varying tangential component of H-field let us apply the Ampere's circuital law (66) along the rectangular path as the closed loop in figure (b). If its height dh is made infinitesimally small then the only contribution to the line integral of the left side of (62) is along the top and bottom edges of length dL and second term of the right hand side becomes zero as the area dLxh is vanishingly small.

Then

L

H

dl

=

H

1

•−

(

dL

)

+

H

2

(

dL

)

=−

H

1t

dL

+

H

2t

dL

=

KdL

leads to H 2t -H 1t =K

(80)

where a sheet of current having a linear current density of K A/m width is also assumed at the interface of the two media. Since the Gauss's law for time varying electromagnetic field for E and B remain same as those for static field, the boundary conditions for normal components of E and B remain uncharged.

t

M. M. ALI Page No.:8/11 ρ
s
∆h

1

2

(a) B 1
H 1
dS
K
dt
⊕⊕⊕
dh
dS
dL
H 2

(b)

3.8 Potential due to time varying field (Retarded Potential)

From Faraday’s law for time varying field (62),

E

∇× =−

 d B =− d ( ∇× A ) ⇒∇× + E d A dt dt ( dt )

=

∇ × E = −

0

dB

dt

, and B=×A we have

Now from the vector identity ×f=0 or ×-f=0, we may define

d

d

A

A

E +

= −∇

V

⇒ = −∇

E

V

dt

dt

(81)

In static case dA/dt=0, (81) reduces to E= - V and hence E can be determined from V alone. For time varying case E is a function of both V and A. In time varying case A can not be determined from (51) or (55). Similarly, V is not also the solution of 2 V= - ρ v /ε. From (70) we have

 ∇× B = J d D ⇒∇×∇× A = J d E J d ( −∇ V − d A dt ) µ + µ dt + µ µε dt = + µ µε dt ∇∇• −∇ = ( A ) 2 A J −∇ ( dV ) − d 2 A µ µε dt µε dt 2

However, it is easy to prove from (16), (32) and (51) that A= -µεdV/dt

d

2

A

2

2

∴∇ A µε

=−µ J

(82)

(83)

dt Again from D= ρ v we have

E= ρ v /ε ⇒ ∇ • ( −∇V

The solution of eq (82) and (83) are of similar type and it is easy to solve them in frequency domain. Therefore the fields are assumed to be a function of exp(jωt). Now from (82) we have

 d A = ρ v 2 ⇒ ∇ − V d 2 V = − ρ v dt ) ε µε dt 2 ε

∴ ∇ A + µ εω A = − µ J ⇒ ∇ A + β A = − µ J

2

2

2

2

M. M. ALI Page No.:9/11

(84)

where β 2 = µεω 2 = ω 2 /c 2 . Here c is the light velocity in the media whose permittivity and permeability are ε and µ, respectively. To find the solution let us consider a point source J=J z a z which is function only of radial distance. Then (84) takes the following form

2

2

A +β A =−µ J

z

z

z

1

d

(

r

2

dA

z

r

2

dr

dr

)

+β

2

A

z

=−µ

J

z

(85)

At points far from the source (85) takes the following form

1

d

(

r

2

dA

z

r

2

dr

dr

)

+

β

2

A

z

=

0

(86)

Now if we assume A z =f/r, the dA z /dr=r -1 df/dr – r -2 f and (86) becomes

d

2

f

2

+

β

2

f

= 0

(87)

dr Since f=C exp(-jβr) is the solution of (87), therefore A z = C exp(-jβr)/r. In order to determine C, let us integrate both sides of (85) over a small spherical volume of radius r 0 .

2

A +

z

β

2

A

=−

z

µ

J

z

⇒ ∇•∇

A dv

z

V

=−

β

2

⇒ ∇

V

2

V

A dv

z

A dv

z

µ

z

=−

J dv

β

2

V

A dv

z

⇒ ∇

A

V S

z

µ

V

dS

J dv

z

a r

=−

β

2

V

A dv

z

µ

V

J dv

z

(88)

Now A z a r =dA z /dr= - (1+j βr)Cexp(-jβr)/r 2 . Therefore in the limit r 0 tends to zero

S

A

z

dS

a

r

=

lim

r

0

0

2

π π

∫∫

0

0

[

(1

+

β

j

r

0

)

C

exp(

β

j

r

0

)sin

θθφ

d

d

=−

4

C

π

Again since dv=r 2 sinθdθdφ, and A z varies as 1/r, consequently, if r 0 is vanishingly small the volume integral of A z in (88) vanishes. Therefore,

 J dv A = µ ∫ J z exp( − β j ) r dv z ⇒ z 4 π V µ J exp( 4 π V − j β r ) dv r µ J exp( j ω t − β j r ) dv ( r ) = 4 π ∫ V r ⇒ A ( r , t ) = 4 π ∫ V r r , t ) µ = ∫ J exp j ( ω t − r / c ) dv = µ ∫ J ( t − r / c ) dv 4 π V r 4 π V r

= µ

C

A

A (

Similarly, the solution of (83) can be obtained as

V

1

V

ρ

(

t

r

/

)

c dv

(

r t

,

) =

4

πε

r

(89)

(90)

3.9 Power flow and the Poynting Vector

The unit of E is volt/m and that of H is A/m, therefore the product of their magnitudes have the unit of power density. The flow of power due to electromagnetic field in a particular direction is of prime importance, the vector product of E and H is used to determine the power of an electromagnetic wave. If we define the power density vector as P=E×H Watt/m 2 .

M. M. ALI Page No.:10/11

Now ∇•P=∇•( E×H)= H(∇×E) - E(∇×H) Using the Maxwell’s equations we have ∇•P=H(-dB/dt) - E(J+dD/dt) -∇•P=µH(dH/dt) + EJ+εEdE/dt Watt/m 2 (91) Eq (91) is known as the point form of poynting theorem. Integrating both sides of (91) over some volume v and applying the divergence theorem, we obtain the integral form of poynting theorem as follows

V

or

∇•

 P dv E • J dv ⎛ H ⎜ µ d H + E • d E ⎞ ⎟ dv = ∫ V + ∫ V ⎝ • dt ε dt ⎠ ∫ P • d s = ∫ E • J dv + ∫ ⎛ ⎜ H µ • d H + E • ε d E ⎞ ⎟ s V V ⎝ dt dt ⎠

dv

watt

(92)

The term on the side of (92) is the net inward flux of P into the volume v. The first term on the right side of (92) is a power dissipation term in that it represents the rate of expenditure of energy by the electric field. The second term on the right side of (92) is given by

V

µH

d

H

d

E ⎞ ⎟

d

(

1

1

dt

dt

dt

2

2

+

E

ε

dv

=

V

H

µ

2

+

E

ε

2

)dv

and represents the time rate of increase of energy stored in the magnetic and electric fields respectively in the volume v. Therefore (92) states that the net inward flux of the poynting vector through some closed surface is the sum of the power dissipated in the volume enclosed by the surface and the rate of change of energy stored in the volume enclosed by the surface.

3.10 Poynting Vector in phasor form

The poynting vector can be expressed in phasor form as follows:

P ˆ = E× ˆ H ˆ

The density of average flow is then 1
ˆ 1
=
Re[
P
]
=
Re[
E× ˆ H ˆ
]
.
P av
2
2
This can be proved as follows:
1
ˆ
j
ω
t
ˆ
ω
t
ˆ
j
ω
t
E
=
Re(
E
e
)
=
( E
e j
+
E
e
)
2
1
ˆ
j
ω
t
ˆ ˆ
j
ω
t
j
ω
t
H
=
Re(
H
e
)
=
( H
e
+
H
e
)
2
1
1
ˆ
j2
ω
t
j2
ω
t
∴ P = E × H
=
(
E ˆ × H ˆ
+ E ˆ × H +
)
( E ˆ × H ˆ
e
+ E ˆ
× H ˆ
e
) (93)
4
4
Since
(E ˆ
× H ˆ
) ∗
=
E ˆ
×
H ˆ
and E ˆ
×
H ˆ
=
( E ˆ
×
H ˆ
)
(93) can be written as
1
1
j2
ω
t
j2
ω
t
P =
(
M ˆ + M ˆ
)
+
( N ˆ
e
+ N ˆ
e
)
(94)
4
4
ˆ
ˆ
where M
=
E ˆ
×
H ˆ
and
N ˆ
=
E ˆ
×
H and we obtain from (94)

P

=

=

1

Re(

ˆ

M

1

Re(

ˆ

N e

j

2

ω t

Re( E ˆ

×

+

H ˆ

+

2

1

2

Re( E ˆ

2

)

1

2

)

)

×

P

av

=

1

T

1

T

2

0

P

dt

=

Re(

ˆ

E

×

ˆ

H

H ˆ e

)

j

2

t

ω

)

M. M. ALI Page No.:11/11

(95)

because the time average of the second term within one period is zero.